THE INFLUENCE OF VIRAL MARKETING THROUGH TIKTOK ON CONSUMERS’ ATTITUDE AT SHOPEE - Indrawati Indrawati; M Rasyad Rizqullah (Journal of Global Business and Management Review, 2022)
This study was conducted to determine the influence of Shopee's Viral Marketing in TikTok on consumers’ attitude at Shopee. The purpose of this study is to explain how informativeness, entertainment, irritation, credibility of Shopee's viral marketing video on TikTok and their influence consumers’ attitudes in the video. This study uses quantitative methods with descriptive - causal purposes. Non-probability sampling has been used in this study with the type of purposive sampling. The number of respondents were 275 people. The data analysis technique used is descriptive analysis and SEM-PLS analysis using the SmartPLS 3.0. Based on the results of the descriptive analysis Informativeness, Entertainment, and Credibility, they are in the good category, while Irritation is in the not good category. The consumers’ attitude variable is in the good category. The results of the SEM-PLS analysis show that informativeness, entertainment, and credibility have a positive significant influence on consumer attitudes, while irritation has no significant influence on consumers’ attitude.